1999
DOI: 10.1577/1548-8675(1999)019<1028:lhbdrt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Low-Head Barrier Dams Restrict the Movements of Fishes in Two Lake Ontario Streams

Abstract: The Great Lakes Fishery Commission (GLFC) is considering greater use of low‐head barrier dams on stream tributaries of the Laurentian Great Lakes to control populations of sea lampreys Petromyzon marinus. The impact of these barriers on nontarget fishes is not known. A mark–recapture study on four Lake Ontario streams examined movements of fishes in streams with (barrier) and without (reference) low‐head barriers. A significantly lower proportion of fishes moved across a real barrier on barrier streams than ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 20 publications
1
76
1
Order By: Relevance
“…Low-head dams may block the migratory pathway of fish and thereby cause the local extinction of fish species and the decrease of species richness in the stream segments upstream (Winston et al 1991;Porto et al 1999). The impacts of low-head dams on fish species are perhaps associated with species traits (e.g., swimming ability) (Helfrich et al 1999).…”
Section: Influences Of Low-head Dams On Fish Assemblagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-head dams may block the migratory pathway of fish and thereby cause the local extinction of fish species and the decrease of species richness in the stream segments upstream (Winston et al 1991;Porto et al 1999). The impacts of low-head dams on fish species are perhaps associated with species traits (e.g., swimming ability) (Helfrich et al 1999).…”
Section: Influences Of Low-head Dams On Fish Assemblagesmentioning
confidence: 99%
“…Till now, the pattern of how low-head dams impact fish assemblages still remains debated and unclear (Gillette et al 2005;Poulet 2007). Winston et al (1991) and Porto et al (1999) found the obstacle role of low-head dams on fish passage, resulting in the local extinction of migratory fish. Helfrich et al (1999) discovered that fish species traits (e.g., swimming ability) appeared to be related to low-head dam passage, and they observed the cumulative effect of multiple low-head dams on fish assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality, stress by handling and tag losses are among the causes of low recapture rates (Porto et al, 1999;Smithson, Johnston, 1999 Josephson et al, 2008;Carvalho-Souza et al, 2010;Soula et al, 2012) as well as low mortality caused by tagging procedures (e.g. Riley et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In rivers around the world, countless instream structures are barriers to fish passage (Porto et al 1999;Pringle et al 2000). Movement, whether short distances between habitat patches or long migrations in streams, is vital to survival and reproductive success of many stream fishes (Pringle et al 2000).…”
mentioning
confidence: 99%
“…Over time, restricted fish passage may result in reduced fish abundance and species richness (Joy and Death 2001), fragmentation of populations and genetic divergence (Pringle et al 2000;Morita and Yamamoto 2002), shifts in fish assemblages in areas upstream and downstream from impoundments (Taylor et al 2001;Gehrke et al 2002), and possible extirpation of species in reaches upstream from barriers (Winston et al 1991;Taylor et al 2001). Although a great deal of past research has investigated fish passage through large barriers (i.e., dams built for hydroelectricity production and reservoir construction) and the corresponding changes in river fish communities resulting from these impoundments, small structures, such as low-head dams and road crossings, also present serious barriers to fish passage that may adversely affect fish populations and communities (Warren and Pardew 1998;Porto et al 1999;Ovidio and Philippart 2002;Santucci et al 2005).…”
mentioning
confidence: 99%